The theoretical evaluation of estradiol electrochemical determination, assisted by a new triazolic schiff base - Tkach, V. V.; Storoshchuk, N. M.; de Oliveira, S. C.; Kopiika, V. V.; Luganska, O. V.; Parchenko, V. V.; Bigdan, O. A.; Genç, M.; Yagodynets, P. I.; Луганська, О. В.; Парченко, Володимир Володимирович; Бігдан, Олексій Антонович (My University, 2019)
The possibility of estradiol electrochemical determination on an anode, modified by a new triazolic Schiff base, has been theoretically evaluated. The correspondent mathematical model has been developed and analyzed by means of linear stability theory and bifurcation analysis. It was shown that the Schiff base provides an efficient estradiol electrochemical determination in neutral and basic media. The proper basicity of Schiff base and triazolic ring favors the process. The steady-state stability is easy to establish. The oscillatory behavior, in this case, is possible, due to the double electric layer influences of the electrochemical stage.
Keywords: ovarian hyperstimulation syndrome; estradiol; electrochemical sensors; chemically modified electrodes; fumigatin; stable steady-state